Assessment of ceramic based photocatalytic as indoor air purifier during covid-19 pandemic. Issue 1 (1st February 2022) - Prasetya, H; Agustina, L; Rinovian, A; Muttaqin, F D
Abstract: In reducing number people who exposed covid-19, Government of Indonesia (GOI) have been issued micro-scale people activities limitation policy. Based on the policy, most people activities should be carried out in indoor area, called Work from Home (WFH). Indoor activities are at risk of expose to air pollution if there is a pollution source and unhealthy air circulation. Air purifier need develop to degrade pollution and inhibit microorganism. One of the promising technologies in air purification is Photocatalytic. Photocatalytic is an eco-friendly technique that emerged as a promising alternative for the degradation both organic and non-organic pollutants. Ceramic material (compared to aluminum and stainless steel) composited with Titanium dioxide (TiO2 ) has been investigated to have potential as an optimal photocatalytic medium. Aim of this study was to explore ability of ceramic based photocatalytic in degrade non-organic air pollutant. Earthenware ceramic was coated with photocatalyst material and examined their photocatalytic activation. A simple photo-reactor was established, to investigated performance of ceramic based photocatalyst air quality improvement which was contaminated with cigarette smoke. Result of the study was earthenware ceramic based photocatalyst able to improve air quality by reducing concentration of pollutants both physical and chemical parameters significantly.